2017
DOI: 10.3390/su9060942
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Consumption Dilemmas

Abstract: Abstract:To examine which considerations play a role when individuals make decisions to purchase sustainable product varieties or not, we have conducted a large scale field experiment with more than 600 participating households. Households can vote on whether the budgets they receive should only be spent on purchasing the sustainable product variety, or whether every household in a group is free to spend their budget on any product variety. By conducting several treatments, we tested whether people tend to vie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 48 publications
(42 reference statements)
0
18
0
2
Order By: Relevance
“…Recently, Claudy, Peterson, and O'Driscoll () empirically showed that behavioural reasoning theory (BRT), the key premise of which is that people use different and distinct psychological processes when making behavioural decisions, can successfully explain consumer behaviour in regard to the adoption of renewable energy and overcoming the attitude‐behaviour gap. Vringer, Vollebergh, van Soest, van der Heijden, and Dietz () designed and conducted a quasi‐experiment to test the attitude‐behaviour gap for two familiar products with two distinct sustainability problems: animal welfare in relation to meat and poverty in relation to chocolate. Their analysis of the results suggested that this gap could be overcome by sharing the fact that others buy sustainable products, because people are more inclined to buy sustainable product varieties if they think others are buying them, too.…”
Section: Previous Researchmentioning
confidence: 99%
“…Recently, Claudy, Peterson, and O'Driscoll () empirically showed that behavioural reasoning theory (BRT), the key premise of which is that people use different and distinct psychological processes when making behavioural decisions, can successfully explain consumer behaviour in regard to the adoption of renewable energy and overcoming the attitude‐behaviour gap. Vringer, Vollebergh, van Soest, van der Heijden, and Dietz () designed and conducted a quasi‐experiment to test the attitude‐behaviour gap for two familiar products with two distinct sustainability problems: animal welfare in relation to meat and poverty in relation to chocolate. Their analysis of the results suggested that this gap could be overcome by sharing the fact that others buy sustainable products, because people are more inclined to buy sustainable product varieties if they think others are buying them, too.…”
Section: Previous Researchmentioning
confidence: 99%
“…Sustainable Consumption Dilemmas [3] considers both the social dilemma and moral dilemma aspects of sustainable consumer behaviour with respect to meat consumption. Unlike most studies, real behaviour has been studied in a large-scale field experiment in which participants received credit which was large enough to cover the extra costs of buying organic meat as compared with conventional meat.…”
Section: Macro and Meso Views On Sustainable Consumer Behaviourmentioning
confidence: 99%
“…As environmental problems become worse, consumers become more inclined towards sustainable consumption. Contrary to this, consumers also suffer from a consumption dilemma where sustainable consumption is not realistic (Vringer, Vollebergh, van Soest, van der Heijden, & Dietz, ). To encourage green consumption, many researchers have studied attitude‐behaviour gaps in pro‐environmental product purchases (Burke, Eckert, & Davis, ; Claudy, Peterson, & O'Driscoll, ; Hess, Stathopoulos, & Daly, ; Jung, Chan‐Olmsted, Park, & Kim, ; Olson, ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%